2024
DOI: 10.1007/s10787-023-01418-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective potential of Erigeron bonariensis ethanolic extract against ovariectomized/D-galactose-induced memory impairments in female rats in relation to its metabolite fingerprint as revealed using UPLC/MS

Weam W. Ibrahim,
Rabab H. Sayed,
Mohamed F. Abdelhameed
et al.

Abstract: Erigeron bonariensis is widely distributed throughout the world's tropics and subtropics. In folk medicine, E. bonariensis has historically been used to treat head and brain diseases. Alzheimer’s disease (AD) is the most widespread form of dementia initiated via disturbances in brain function. Herein, the neuroprotective effect of the chemically characterized E. bonariensis ethanolic extract is reported for the first time in an AD animal model. Chemical profiling was conducted using UPLC–ESI-MS analysis. Femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the potential of clinical drugs that target the Foxo3a signaling pathway to effectively counter COI. Utilized in clinical settings, Chinese herbal medicines or compound formulas such as E. bonariensis, Chaigui granules, and Banxia Xiexin Decoction have exhibited neuroprotective effects by modulating Foxo3a expression in brain tissues, thereby enhancing cognitive function ( Shi et al, 2023 ; Tian et al, 2023 ; Ibrahim et al, 2024 ). Additionally, the anti-malarial drug 8-aminoquinoline has demonstrated robust biological activity in improving neuronal mitochondrial function through the SIRT1/3-Foxo3a pathway ( Ruankham et al, 2023 ).…”
Section: Clinical Prospectivementioning
confidence: 99%
“…Several studies have demonstrated the potential of clinical drugs that target the Foxo3a signaling pathway to effectively counter COI. Utilized in clinical settings, Chinese herbal medicines or compound formulas such as E. bonariensis, Chaigui granules, and Banxia Xiexin Decoction have exhibited neuroprotective effects by modulating Foxo3a expression in brain tissues, thereby enhancing cognitive function ( Shi et al, 2023 ; Tian et al, 2023 ; Ibrahim et al, 2024 ). Additionally, the anti-malarial drug 8-aminoquinoline has demonstrated robust biological activity in improving neuronal mitochondrial function through the SIRT1/3-Foxo3a pathway ( Ruankham et al, 2023 ).…”
Section: Clinical Prospectivementioning
confidence: 99%